Association analysis of ACE, ACTN3 and PPARGC1A gene polymorphisms in two cohorts of European strength and power athletes - Gineviciene, V.; Jakaitiene, A.; Aksenov, M. O.; Aksenova, A. V.; Druzhevskaya, A. M.; Astratenkova, I. V.; Egorova, E. S.; Gabdrakhmanova, L. J.; Tubelis, L.; Kucinskas, V.; Utkus, A. (Biology of Sport, 2016)
The performance of professional strength and power athletes is influenced, at least partly, by genetic components. The main aim of this study was to investigate individually and in combination the association of ACE (I/D), ACTN3 (R577X) and PPARGC1A (Gly482Ser) gene polymorphisms with strength/power-oriented athletes` status in two cohorts of European athletes. A cohort of European Caucasians from Russia and Lithuania (161 athletes: by groups - weightlifters (87), powerlifters (60), throwers (14); by elite status - `elite` (104), `sub-elite` (57); and 1,202 controls) were genotyped for ACE, ACTN3 and PPARGC1A polymorphisms. Genotyping was performed by polymerase chain reaction and/or restriction fragment length polymorphism analysis. Statistically significant differences in ACTN3 (R577X) allele/genotype distribution were not observed in the whole cohort of athletes or between analysed groups separately when compared with controls. The odds ratio for athletes compared to controls of the ACE I/I genotype was 1.71 (95% CI 1.01-2.92) in the Russian cohort and for the ACE I/D genotype it was 2.35 (95% CI 1.10-5.06) in the Lithuanian cohort. The odds ratio of being a powerlifter in PPARGC1A Ser/Ser genotype carriers was 2.11 (95% CI: 1.09-4.09, P = 0.026). The ACTN3 (R577X) polymorphism is not associated with strength/power athletic status in two cohorts of European athletes. The ACE I/I genotype is probably the `preferable genotype` for Russian athletes and the ACE I/D genotype for Lithuanian strength/power athletes. We found that the PPARGC1A (Gly482Ser) polymorphism is associated with strength/power athlete status. Specifically, the PPARGC1A Ser/Ser genotype is more favourable for powerlifters compared to controls.